A clínica dos casos difíceis no imaginário de estudantes de psicologia - Cambuí, Heloisa Aguetoni; Ribeiro, Diana Pancini de Sá Antunes [UNESP] (Universidade Estadual de Londrina, 2014)
The conducts that occur in the context of intersubjectivity are arranged from unconscious psychological fields which influence individual and collective practices. Therefore, it becomes important to consider the collective imagination of psychology students as this may interfere about the exercise of their clinical practice. The aim of this study was to investigate the collective imaginary of psychology students about the clinical practice with patients considered difficult in the analytic setting. Based on the psychoanalytic method, this research utilized the Procedure of Drawings-Stories with Theme in group interview, for the purpose of discuss on the vicissitudes of contemporary clinical work with these patients. In the present study, participated eight undergraduates of the eighth semester of a psychology course.The resulting material of the interview constituted by drawings-stories and the narrative was psychoanalytically analyzed, in the light of the Multiple Fields Theory proposed by Herrmann and in dialogue with the winnicottian thought, allowing to apprehend the follows fields of affective-emotional meaning: “Insecurity”, “Perfect Therapist”, “Mutuality”, “Experience”, “Negation of Madness” and “Madness as tal”. In general the imaginary manifestations of psychology students constitute the analytic relationship with the difficult patients by mobilizing feelings of insecurity, distress, anxiety, incapacity and helplessness.

As condutas que ocorrem no contexto da intersubjetividade são organizadas a partir de campos psicológicos não conscientes, que influenciam as práticas individuais e coletivas. Torna-se importante, portanto, considerar o imaginário coletivo dos psicólogos em formação, na medida em que este pode interferir no exercício de sua prática clínica. Este estudo teve como objetivo investigar o imaginário coletivo de terapeutas em formação sobre o atendimento de pacientes considerados difíceis no setting analítico. Com base no método psicanalítico, esta investigação utilizou o Procedimento de DesenhosEstórias com Tema em entrevista grupal, com a finalidade de problematizar sobre as vicissitudes da clínica contemporânea com estes pacientes. Participaram deste estudo, oito graduandos do oitavo semestre de um curso de psicologia. O material resultante da entrevista constituído pelos desenhosestórias e a narrativa foi psicanaliticamente analisado, à luz da Teoria dos Campos proposta por Herrmann e em interlocução com o pensamento winnicottiano, permitindo a apreensão dos seguintes campos de sentido afetivo-emocional: “Insegurança”, “Terapeuta Perfeito”, “Mutualidade”, “Vivência”, “Negação da Loucura” e “A Loucura como Tal”. De modo geral, as manifestações imaginárias dos estudantes de psicologia configuram a relação analítica com os pacientes difíceis, por meio da mobilização de sensações de insegurança, angústia, ansiedade, incapacidade e impotência
The clinical practice with difficult patients in the collective imaginary of psychology students
Keywords: Psychoanalysis; Winnicott; Difficult patients; Procedure of drawings-stories with theme; Collective imaginary; Winnicott; Procedimento de Desenhos-Estórias com Tema; Imaginário coletivo; Pacientes dificeis; Estudantes de Psicologia